Financing the Boom in Public-Private Partnerships in Indian Infrastructure : Trends and Policy Implications - Harris, Clive; Kumar, Sri Tadimalla (World Bank, Washington, DC, 2012)
India has seen rapid growth in recent years in its program of infrastructure public-private partnerships (PPPs). Despite the surge in demand for finance, local financial markets coped well over the period to 2007 and even offered better terms as they became more used to the PPP model. But areas of possible concern have developed. Gearing has increased significantly, and financing terms mean that PPPs are more exposed to interest rate volatility causes for concern in a period of rising rates and reduced liquidity. Further growth in PPPs will likely require a broadening of the sources of financing once the present financial market turmoil has lessened. Addressing these concerns will call for policy reforms to capital markets and concession frameworks.